KEKUATAN DAN PELUANG REAKTUALISASI KODE ETIK GURU MENUJU MASYARAKAT ACEH YANG BERMARTABAT - Ridhwan M Daud (FITRAH was published by the Center for Research and Community Service (LP2M) Ar-Raniry Islamic State University Banda Aceh, 2021)
The quality of education in Aceh has weakened in recent years. This can reduce the dignity of the Acehnese people compared to the former sultanate period. One way to restore this dignity and worth is to improve the quality of education; and one way to improve the quality of education is by re-actualizing the teacher's code of ethics in the learning process in schools and madrasas. The Islamic attitude of the Acehnese people, graduates of Dayah and UIN Ar-raniry is a big force in realizing the re-actualization of this teacher's code of ethics. The reformation era that has started since 1998, Law Number 44 of 1999 and Law Number 18 of 2001 which established Aceh as an Islamic law area. The Law of the Republic of Indonesia Number 11 of 2006 which stipulates Aceh as a special autonomous region and the formation of the Aceh Education Qanun Number 11 of 2014 concerning Education Providers is a great opportunity to implement this. The steps that need to be taken in this re-actualization are that the teacher must study, understand, appreciate and implement this entire code of ethics. Knowledge of the science of educational tools must also be mastered. In the end, rewards and punishments still need to be given to teachers and education staff who don't want to heed them. The obstacle that may be faced is that not all teachers understand and live up to this code of ethics. However, this can be overcome by conducting planned seminars, workshops and trainings.